Towards Sustainability: Environmental Education in China - A German Strategy for Chinese Schools? - Caterina Wasmer (Universität Duisburg-Essen, Forschungsinstitut für Wirtschaftliche Entwicklungen im Pazifikraum (FIP), 2005)
In the last years China has recognized the environment as an economically valuable good, thus promoting sustainable economic development. Among the young people, this principle is spread by creating awareness through Environmental Education (EE) in schools. Although high on the agenda, the implementation of EE is restricted by a lack of finance and know-how so that Chinese schools benefit from foreign assistance. The focus of this paper is to evaluate the situation of EE in Chinese schools and to test the adaptability of a German EE strategy in China. For this purpose, the need patterns of different categories of schools concerning the contents and the implementation of EE are analyzed. These need patterns are then contrasted with the contents and concept of the German EE strategy. The restrictions in adaptability as well as the necessary adaptations of the German strategy are concluded and laid down accordingly. Together with an outline of possible project partners, these findings are put together to form four different project proposals for EE projects in Chinese schools.
Keywords: 330; Sustainability; China; Environmental Education; Feasibility Study; Bildung; Umweltbewusstsein; Kulturelle Beziehungen; Deutsch; China